Pengaruh Pendidikan Kesehatan Dengan Menggunakan Audiovisual Terhadap Pengetahuan Pemeriksaan Sadari Pada Mahasiswi ITEKES Muhammadiyah Kalimantan Barat - Hanafi; Rafika, Ita (Indra Institute Research & Publication, 2023)
Breast cancer is a health problem and cause of death for women today both in Indonesia and throughout the world, the prevalence of breast cancer in the world is 508,000 deaths (World Health Organization, 2013). Objective: This research aims to see the influence of Health Education on examining BSE knowledge in ITEKES Muhammadiyah West Kalimantan students. Methodology: This research uses a pre-experimental method with a pre-post test without control, the sampling technique in this research uses total sampling. Research Results: The results of the Wilcoxon statistical test show (p value = 0.000 p value < 0.000, meaning that there is an influence of Health Education on the level of examination of BSE knowledge before and after being given health education using the audiovisual method. Conclusion: There is a difference in the level of knowledge before and after being given Health Education using the audio-visual method regarding SADSARI knowledge of West Kalimantan Muhammadiyah ITEKES students.